Wages and foreign ownership a comparative study of Mexico, Venezuela, and the United States - Aitken, Brian; Harrison, Ann E.; Lipsey, Robert E. 1926-2011 (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1995)
This paper explores the relationship between wages and foreign investment in Mexico, Venezuela, and the United States. Despite very different economic conditions and levels of development, we find one fact which is robust across all three countries: higher levels of foreign investment are associated with higher wages. In Mexico and Venezuela, foreign investment was associated with higher wages only for foreign-owned firms -- there is no evidence of wage spillovers leading to higher wages for domestic firms. In the United States there is evidence of wage spillovers. The lack of spillovers in Mexico and Venezuela is consistent with significant wage differentials between foreign and domestic enterprises. In the United States, wage differentials are smaller.